2008
DOI: 10.1111/j.1600-0501.2007.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin levels in peri‐implant crevicular fluid

Abstract: The findings of this preliminary study suggest that the crevicular fluid level of OPG deserves further investigation as a possible marker to evaluate the health status of surrounding tissues of dental implants, as this was not the case for the sRANKL level. Larger scale studies, particularly in peri-implantitis cases, may shed more light on this subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
(56 reference statements)
5
45
0
Order By: Relevance
“…Similar to findings in GCF obtained from sites with periodontitis (Belibasakis and Bostanci 2012), there is increasing evidence showing the association of the receptor activator of nuclear factor kappaB ligand (RANKL) -osteoprotegerin (OPG) system with the occurrence and severity of periimplantitis (Arikan et al 2008;Arikan et al 2011;Sarlati et al 2010;Guncu et al 2012;Duarte et al 2009a;Duarte et al 2009b;Rakic et al 2013). A few studies looking into other markers of bone metabolism, such as osteocalcin, reported that these are higher in PICF from peri-implant mucositis compared to healthy sites, whereas no differences were observed between periimplatitis and either mucositis or health.…”
supporting
confidence: 55%
“…Similar to findings in GCF obtained from sites with periodontitis (Belibasakis and Bostanci 2012), there is increasing evidence showing the association of the receptor activator of nuclear factor kappaB ligand (RANKL) -osteoprotegerin (OPG) system with the occurrence and severity of periimplantitis (Arikan et al 2008;Arikan et al 2011;Sarlati et al 2010;Guncu et al 2012;Duarte et al 2009a;Duarte et al 2009b;Rakic et al 2013). A few studies looking into other markers of bone metabolism, such as osteocalcin, reported that these are higher in PICF from peri-implant mucositis compared to healthy sites, whereas no differences were observed between periimplatitis and either mucositis or health.…”
supporting
confidence: 55%
“…Lappin et al (2007) reported decreased serum OPG levels and greater soluble receptor activator of nuclear-factor kappa B ligand (sRANKL) sRANKL/OPG ratios in smoker patients in the maintenance program than the non-smoker counterparts. Negative correlation between pack-years and total OPG amount in peri-implant crevicular fluid was detected in clinically healthy implants (Arıkan et al 2008). Our recent finding of higher sRANKL, lower OPG concentrations in saliva of untreated/treated smokers than non-smokers confirmed these findings.…”
Section: Introductionsupporting
confidence: 79%
“…This result, however, was not correlated with clinical signs. At the same time, Arikan et al (2008Arikan et al ( , 2011 observed that OPG is a potential marker to assess implant conditions and its local levels may help to distinguish diseased and healthy implants. Another marker that could represent the destruction of tissues-pyridinoline cross-linked carboxyterminaltelopeptide of type I collagen (ICTP)-has been evaluated in previous clinical studies.…”
Section: Discussionmentioning
confidence: 99%